Conceptual Review of Qira’ah Mubadalah on the Phenomenon of Domestic Violence - Nela Rahmaniya Nur Faizah (Values: Jurnal Kajian Islam Multidisiplin, 2025)
Domestic violence remains a serious issue both in Indonesia and globally, often legitimized by patriarchal biases. This study aimed to conceptually investigate the perspective of Qira'ah Mubadalah as a method capable of addressing the phenomenon of domestic violence through the values of reciprocity and equality. Utilizing a qualitative-conceptual research method, this study explores hierarchical relationships and contemporary perspectives on domestic violence. The findings reveal that Qira'ah Mubadalah offers an alternative interpretation that emphasizes equitable and reciprocal relations between husband and wife. It provides practical solutions for preventing domestic violence by rejecting discriminatory interpretations of religious texts and promoting a reading that positions both men and women as equal subjects. This approach considers the principles of maqāṣid al-sharī‘ah, values of rahmah (compassion), and substantive justice, thereby contributing to the construction of a domestic relationship paradigm free from violence.